Characterization and Fine Mapping of a Leaf Wilt Mutant, m3, Induced by Heavy Ion Irradiation of Rice. Issue 6 (1st November 2019) - Peng, Xin; Luo, Lixin; Cui, Huan; Wang, Hui; Guo, Tao; Liu, Yongzhu; Wang, Jiafeng; Huang, Ming; Yang, Guili; Chen, Zhiqiang; Xiao, Wuming
ABSTRACT: A rice ( Oryza sativa L.) mutant, named m3, was isolated from a population of the M2 generation derived from an indica accession, BBS, where the seeds of BBS were treated with carbon ion irradiation at a dosage of 100 Gy to produce mutants. The m3 mutant is primarily characterized by the production of abnormal wilted leaves by appearance on the main stem, and additional tillers at the 9‐leaf stage. This abnormal leaf‐wilt phenotype is temporary, persisting only to the 13‐leaf stage, after which subsequent new leaves on the main stem and tiller appear normal. The phenotypic change of m3 during the 9‐ and 13‐leaf growth stages was further confirmed at physiological and biochemical levels. Additionally, compared with the wild type (WT, BBS), the heading date of m3 was noticeably delayed. The numbers of grains per panicle were lower by 32.44% than that of the WT. Moreover, plant height, width of flag leaf, panicle weight per plant, panicle length, and seed‐setting rate of m3 were considerably lower than those of the WT. Our genetic analysis revealed that the mutant phenotype of m3 was controlled by a single recessive gene, designated m3(g) . We used recessive F2 individuals and mapped the m3(g) locus to a 3824‐kb region near the centromere of chromosome 11. We also performed a MutMap approach to refine the m3(g) locus to a 1030‐kb region comprising 115 genes, but six genes show nonsynonymous mutations. This study provides essential information for the cloning of the m3(g) gene and demonstrates that the MutMap approach is powerful enough to map a target gene that is located in centromeric regions.